The Role of The Cochrane Collaboration in Support of the WHO Nutrition Guidelines(1)(2) - Tovey, David (American Society for Nutrition, 2014)
This article describes the background and contribution of The Cochrane Collaboration to the WHO Nutrition Guidelines program. Systematic reviews, augmented by the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methodology for assessing the quality of a body of evidence, form the evidence basis for WHO guidelines. Our shared experience of working together has highlighted a number of issues that are challenging, such as decisions made about selecting appropriate questions for evidence synthesis and the nature of study types that are included, in particular the decision on whether or not to extend a search beyond randomized studies. Although the skills and experience required for evidence synthesis are different from those needed to determine recommendations for policy and practice, our experience suggests that some engagement between the two groups is mutually beneficial. Finally, our experience highlights the recognition that evidence of effectiveness is essential but by no means sufficient to guide decisions on recommendations. Programmatic and implementation considerations are important to guide decision making and the evidence basis for this may be limited; therefore, it is essential that groups involved in delivering interventions to populations are also engaged in the guidelines process.